Anos de vida perdidos por mortalidade: um dos componentes da carga de doenças Years of life lost by mortality: a component of the burden of disease - Fúlvio B Nedel; Maria Rocha; Joaquín Pereira (Universidade de São Paulo, 1999)
OBJETIVO: Calculou-se a carga de doença devida à mortalidade, os anos de vida perdidos por "morte prematura" (AVP), nos Estados do Rio Grande do Sul e Santa Catarina, comparando alguns resultados com o Brasil. MÉTODOS: Baseou-se nos anos de vida ajustados em função da incapacidade (AVAI), indicador que agrega mortalidade e morbidade em uma medida global. As populações de estudo foram os óbitos de residentes nos Estados em 1994 e no Brasil em 1993. RESULTADOS: Embora a maior carga por mortalidade seja imposta por causas ligadas a um estágio mais avançado da transição epidemiológica, tanto o Rio Grande do Sul como Santa Catarina, mas principalmente o Brasil, sofrem importante carga por doenças do subdesenvolvimento. As lesões representam o segundo grupo nos Estados e terceiro no Brasil. CONCLUSÃO: O indicador permite comparar agravos de alta e baixa letalidade, sendo instrumento útil na gestão e controle social das políticas e ações de saúde. INTRODUCTION: The register of death by cause, sex and age groups of residents in 1994 in Rio Grande do Sul (RS) and Santa Catarina (SC), two Brazilian southern states, were studied to calculate the years of life lost (YLL), one of the two components that summarize disability adjusted life years (DALY), in RS, SC and Brazil. METHODS: The methodology employed is the same used in the Global Burden of Disease study to quantify the mortality component (YLL) of DALY in the world. RESULTS: The results show that the greatest proportion and rates caused by Group II (Noncommunicable diseases), linked with more advanced stages of the epidemiological transition, in RS, SC and Brazil. But in both states and especially in Brazil, Group I (Communicable, maternal, perinatal and nutritional conditions) causes an important proportion of YLL. The Group III (Injuries) was the second more important group in RS and SC and the third in Brazil. Road traffic accidents are particularly important in SC, where the intentional injury rate is half than the one in RS. The leading causes of YLL were road traffic accidents, ischemic heart disease and cerebrovascular disease in SC, and ischemic heart disease, cerebrovascular disease and road traffic accidents in RS. CONCLUSIONS: Death certification in the southern region of Brazil has a complete coverage and miscoded death proportion is small, providing a reliable mortality information. DALY allow comparing fatal and nonfatal health outcomes to determine the importance of different diseases and to establish health priorities. DALY are also an useful tool to identify disadvantaged groups, target health interventions and provide information for social control of resource allocation.